Meloxicam Exerts Neuroprotection on Spinal Cord Trauma in Rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; ERZİK, CAN; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (INFORMA HEALTHCARE, 2011)
Traumatic injury to the central nervous system results in the delayed dysfunction and neuronal death. Impaired mitochondrial function, generation of reactive oxygen species (ROS), and lipid peroxidation occur soon after traumatic spinal cord injury (SCI), while the activation of compensatory molecules that neutralize ROS occurs at later time points. The aim of the current study was to investigate the putative neuroprotective effect of the COX2 inhibitor meloxicam in a rat model of SCI. In order to induce SCI, a standard weight-drop method that induced a moderately severe injury (100 g/cm force) at T10, was used. Injured animals were given either 2 mg/kg meloxicam or saline 30 min postinjury by intraperitoneal injection. At seven days postinjury, neurological examination was performed and rats were decapitated. Spinal cord samples were taken for histological examination or determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and DNA fragmentation. Formation of ROS in spinal cord tissue samples was monitored by using a chemiluminescence (CL) technique. SCI caused a significant decrease in spinal cord GSH content, which was accompanied with significant increases in CL, MDA levels, MPO activity, and DNA damage. On the other hand, meloxicam treatment reversed all these biochemical parameters as well as SCI-induced histopathological alterations. Furthermore, impairment of the neurological functions due to SCI was improved by meloxicam treatment. The present study suggests that meloxicam, reduces SCI-induced oxidative stress and exerts neuroprotection by inhibiting lipid peroxidation, GSH depletion, and DNA fragmentation.
Keywords: COX-2; glutathione; lipid peroxidation; meloxicam; neuroprotection; spinal cord injury; OXIDATIVE STRESS; BRAIN-INJURY; CYCLOOXYGENASE-2; GLUTATHIONE; METABOLISM; CONTUSION; DAMAGE; ACID